Trends and inequities in use of maternal health care services in Bangladesh, 1991-2011 - Anwar, Iqbal; Y. Nababan, Herfina; Mostari, Shabnam; Rahman, Aminur; A. M. Khan, Jahangir (© 2015 Public Library of Science, 2016)
This article was published in PLoS ONE [© 2015 Public Library of Science] and the definite version is available at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0120309